China's exports in ICT and its impact on Asian countries - Yuqing Xing (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper analyses China's ICT exports growth in its two major markets Japan and the US from 1992 to 2004. It focuses on ICT products classified in SITC 75, 76 and 77. The empirical results show that Chinese exports had maintained two-digit annual growth during the period. The growth was much higher than the corresponding growth of the overall markets. By 2004, Chinese ICT exports accounted for 26 per cent of the total Japanese imports and 19 per cent of the total imports of the US in ICT products. In addition, the paper investigates whether the rapid growth of Chinese ICT exports crowded out that of other Asian countries: Indonesia, Malaysia, Philippines, Singapore, South Korea and Thailand. The empirical analysis shows that the crowding out effect differs across countries and products. The exports of Singapore and Philippines have been negatively affected by the growth of Chinese exports, but no crowding effect existed at all with Indonesia's exports
Keywords: F1; O5; 330; China; exports; ICT; Asia; IT-Industrie; Export; Internationaler Wettbewerb; China; Asien